2019
DOI: 10.3758/s13428-019-01228-y
|View full text |Cite
|
Sign up to set email alerts
|

Design factors in mouse-tracking: What makes a difference?

Abstract: Investigating cognitive processes by analyzing mouse movements has become a popular method in many psychological disciplines. When creating mouse-tracking experiments, researchers face many design choices-for example, whether participants indicate responses by clicking a button or just by entering the button area. Hitherto, numerous different settings have been employed, but little is known about how these methodological differences affect mouse-tracking data. We systematically investigated the influences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 45 publications
3
69
0
1
Order By: Relevance
“…Cursor acceleration was linearized and cursor speed was slowed down (to 1,400 sensitivity) using the CursorSense© application (version 1.32). Slowing down the cursor ensured that motor behavior was recorded as the acoustic signal unfolded, resulting in a smooth trajectory from start to target (Kieslich, Schoemann, Grage, Hepp, & Scherbaum, 2019).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Cursor acceleration was linearized and cursor speed was slowed down (to 1,400 sensitivity) using the CursorSense© application (version 1.32). Slowing down the cursor ensured that motor behavior was recorded as the acoustic signal unfolded, resulting in a smooth trajectory from start to target (Kieslich, Schoemann, Grage, Hepp, & Scherbaum, 2019).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Such methodological variation is a consequence of a developing approach without agreed standards and has been important in sampling the range of potential paradigms that might be employed. Nevertheless, recent analyses suggest the methodological specifics of mouse-tracking paradigms (i.e., design features) influence the strength of the relationships observed between experimental manipulations and mouse-tracking outcomes (Grage, Schoemann, Kieslich, & Scherbaum, in press;Kieslich, Schoemann, Grage, Hepp, & Scherbaum, 2019;Scherbaum & Kieslich, 2018;Schoemann, Lüken, Grage, Kieslich, & Scherbaum, 2019). We feel the time has come for the field, to scrutinize and advance its methodological ingenuity and to develop new standards for mouse-tracking research which facilitate strong reproducible findings that can more easily be combined across studies (Morey et al, 2016;Munafò et al, 2017;Nosek et al, 2015).…”
Section: Mouse-tracking As a Process-tracing Methodsmentioning
confidence: 99%
“…We reviewed and synthesized recent findings on design features in mouse cursor tracking (Grage et al, in press;Kieslich, Schoemann, et al, 2019;Scherbaum & Kieslich, 2018;Schoemann, Lüken, et al, 2019) that indicate a considerable influence of design factors on cognitive effects as measured by mouse cursor tracking.…”
Section: Are Design Factors Important?mentioning
confidence: 99%
“…However, several data sets, particularly those collected with cameras (e.g., Friedman, Brown, & Finkenbeiner, 2013) or a robotic handle (e.g., Burk et al, 2014) showed relatively homogenous sets of smoothly curved trajectories that might be best described by a single cluster. Other important moderators are characteristics of the study design (for discussions, see Kieslich & Henninger, 2017;Kieslich, Schoemann, Grage, Hepp, & Scherbaum, 2018;Scherbaum & Kieslich, in press;Wulff, Haslbeck, & Schulte-Mecklenbeck, 2018). Figure 5 gives an illustration of the trajectories produced by four hand-picked studies, including the study by Spivey et al (2005; Figure 5a), a mouse-tracking study using a similar methodological setup as Spivey et al (Koop & Johnson, 2013; Figure 5b), a mouse-tracking study using a different methodological setup than Spivey et al (Scherbaum et al, 2010; Figure 5c), and a hand-tracking study using a robotic handle (Burk et al, 2014; Figure 5d).…”
Section: How Prevalent Are Trajectory Types?mentioning
confidence: 99%